2019
DOI: 10.1029/2018wr023576
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability and Temporal Persistence of Event Runoff Coefficients for Cropland Hillslopes

Abstract: Using data collected from collocated hillslopes in central Iowa, the United States, the authors (1) explored the spatial variability of runoff coefficient at the event scale by examining the relationships between the standard deviation and coefficient of variation of runoff coefficient and the mean and (2) analyzed the temporal persistence of spatial pattern of runoff coefficient using Spearman rank and Pearson correlation coefficient. This study considered 12 cropland hillslopes with 0-20% native prairie vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
1
8
2
Order By: Relevance
“…Runoff coefficient ranged from 0.001 to 0.08 in the current study. Surprisingly, runoff coefficient was very low compared with other studies both at the cropland hillslope scale ranging from 0.29 to 1.46 reported by Chen et al (2019) and in the catchment scale ranging from 0.01 to 0.37 determined by Guastini et al (2019). It is anticipated that one of the main reasons for this pronounced difference is that forest residuals such as tree limbs, tops, and foliage left on the skid trails can increase the ground surface roughness and thereby create a b Runoff (mm) Runoff (mm) Fig.…”
Section: Runoffcontrasting
confidence: 67%
“…Runoff coefficient ranged from 0.001 to 0.08 in the current study. Surprisingly, runoff coefficient was very low compared with other studies both at the cropland hillslope scale ranging from 0.29 to 1.46 reported by Chen et al (2019) and in the catchment scale ranging from 0.01 to 0.37 determined by Guastini et al (2019). It is anticipated that one of the main reasons for this pronounced difference is that forest residuals such as tree limbs, tops, and foliage left on the skid trails can increase the ground surface roughness and thereby create a b Runoff (mm) Runoff (mm) Fig.…”
Section: Runoffcontrasting
confidence: 67%
“…For example, Cerdan et al (2004) found mean Rc and σ of 0.05 and 0.045, respectively, for 90 ha catchment in Normandy or Tachecí et al (2013) found the Rc between 0.03 and 0.06 in 0.6 km 2 catchment in the Czech Republic. The magnitude of Rc in HOAL is smaller than what was found on cropland hillslopes in central Iowa (Chen et al 2019) where the median over 70 events was 0.22, or as reported in regional assessments of mesoscale catchments in Austria (the median of Rc varies between 0.18 and 0.43, Merz et al 2006) or Germany (Tarasova et al 2018b). The magnitude of Rc is not related to size or surface slope of sub-catchments in HOAL, which is similar as reported in previous studies of Chen et al (2019) or Cerdan et al (2004).…”
Section: Spatial and Seasonal Variability Of Event Runoff Characteriscontrasting
confidence: 63%
“…The magnitude of Rc in HOAL is smaller than what was found on cropland hillslopes in central Iowa (Chen et al . 2019 ) where the median over 70 events was 0.22, or as reported in regional assessments of mesoscale catchments in Austria (the median of Rc varies between 0.18 and 0.43, Merz et al . 2006 ) or Germany (Tarasova et al .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Such measures have been examined in detail in the Tianmu Lake basin, where up to 75% of TN loads can be retained if appropriate measures are implemented [50]. Small upland ponds and cascading wetlands are both able to strongly buffer nutrient loads in hilly catchments [124][125][126]. The efficacy of the latter has been demonstrated along the Zhangtian River in the Tianmu Lake watershed (Figure 2).…”
Section: Integrative Management To Mediate Nutrient Lossmentioning
confidence: 99%